Consumer Preferences for Spicy Food Sales Channels in Bogor City: Transition from Multichannel to Omnichannel Era - Zhafirah Zhafirah; Popong Nurhayati; Rr. Heny Kuswanti Suwarsinah (Green Publisher Indonesia, 2026)
This study examines consumer preferences for spicy food sales channels in Bogor City within the transition from multichannel to omnichannel marketing. The research aims to identify consumer characteristics, analyze the existing implementation of omnichannel practices, determine preference patterns across sales channels, and provide strategic recommendations for food businesses. Primary data were collected from 100 respondents selected through purposive sampling, targeting consumers aged ≥17 years who enjoy spicy food and have purchased both online and offline. Data were analyzed using descriptive statistics, validity and reliability tests, and conjoint analysis. The results show that consumers prefer multichannel purchasing patterns, with offline store purchases remaining the most favored channel, supported by preferences for direct interaction and cash payments. Price and promotion emerged as the most influential attributes, with exclusive pricing on social commerce being the most preferred option. Consumers also prioritize product availability on online platforms and favor delivery services over click-and-collect features, indicating that full omnichannel integration is not yet essential. The findings reveal that spicy food businesses in Bogor mostly operate under multichannel systems, aligning with consumer tendencies that value independent channel advantages rather than fully integrated experiences. This study recommends strengthening both offline and online channels with differentiated value offerings while gradually preparing the foundation for future omnichannel adoption. The results provide practical insights for business owners, policymakers, and future researchers regarding consumer behavior in the spicy food sector during the digital transformation era.